Contribution of Hydroponic Greenhouse Activities to Household Income of Women Farmers Groups - Fitriani, Naila; Sulaeni, Sulaeni; Sariyoga, Setiawan (Poltanesa, 2025)
This research investigates the role of greenhouse-based hydroponic activities in supporting household income and food security among members of the Women Farmer Group (Kelompok Wanita Tani/KWT) Wahid Sapa in Lebak Gede Village, Pulomerak District, Cilegon City. The study was conducted from September to November 2025, applying a quantitative descriptive approach with a census method involving 30 respondents. Data were collected through structured questionnaires, direct observation, and supporting institutional documents. The research objectives include analyzing women’s labor allocation in hydroponic activities, measuring the income contribution generated from greenhouse cultivation, and identifying its influence on household food security. Data were analyzed using percentage analysis for labor allocation and income contribution, while food security was assessed using the Food Insecurity Experience Scale (FIES). Findings reveal that women actively participated in greenhouse management by allocating a portion of their daily productive time despite fulfilling domestic duties. Hydroponic cultivation contributed economically to household income, although the level of contribution varied among members. Additionally, the activity strengthened household food security through increased access to fresh vegetables and reduced household expenditure on food consumption. These results highlight that greenhouse hydroponics functions not only as a source of supplemental income but also as a strategic empowerment program enhancing women’s economic participation, resource utilization in limited land areas, and resilience toward household food needs.